Highly Circularly Polarized Photoluminescence over a Broad Spectral Range from a Calamitic, Hole-Transporting, Chiral Nematic Glass and from an Indirectly Excited Dye - Woon, K.L.; O'Neill, M.; Richards, G.J.; Aldred, M.P.; Kelly, S.M.; Fox, A.M. (John Wiley & Sons, 2003)
A highly birefringent, luminescent chiral nematic liquid crystal is shown to have an extremely broad photonic stop band (see dashed line in Figure) overlapping its emission spectrum. Highly circularly polarized photoluminescence is observed from the liquid crystal itself and from an indirectly excited dye dopant. The liquid crystal is hole-transporting with a room-temperature mobility of 4 × 10–4 cm2 V–1 s–1.